Literasi Keuangan Melalui Sosial Media pada Wanita Pekerja : Analisis Bibliometrik - GIta Sekar Melati Putri; Indrawati Yuhertiana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the evolution of publications on the topic of financial literacy through social media among working women between 2019-2024, as well as to identify the scholarly articles with the highest number of citations on the topic. Data was collected using Google Scholar with the keywords “financial literacy” and “social media”. Search criteria included article title, abstract, and relevant keywords within 2019-2024. The search results showed 890 journal articles. Of these, 119 articles were further analyzed using VOSviewer 1.6.20 software. Financial literacy through social media is very interesting to be raised as a topic, by appointing working women as the object of research which is also associated with financial behavior variables..